Synthesis, biological evaluation and in silico molecular docking of novel 1-hydroxy-naphthyl substituted heterocycles - El-Sayed; Eman M. Keshk; Aya A. El-Sawi; Mohamed A. Abozeid; Laila A. Abouzeid; Abdel-Rahman H. (Elsevier, 2018)
The versatile precursor 2-acetyl-4-allyl-1-hydroxy naphthalene was synthesized efficiently via Claisen rearrangement 2-acetyl-1-allyloxynaphthalene. The Claisen-Schmidt condensation of latter precursor afforded the corresponding chalcones which were exploited to synthesize a series of potential heterocycles such as pyrazoline, isoxazoline, benzocoumarin and benzoflavone. The synthesized products showed potent antioxidant and antimicrobial activities. Chalcone 3c, naphthyl pyrazoline 6b and hydroxycoumarin 13 exhibited the highest activity as antioxidants. Their binding mode showed specialized recognition of hydroxycoumarin 13 with the triad key amino acids at the active site of the oxidoreductase enzyme (PDB code 1DXO). 1-Hydroxynaphth-2-yl pyrazoline (6b) revealed the highest efficacy against both Gram positive and negative bacterial species. In silico molecular docking of pyrazoline 6b endorsed its proper binding at the active site of the 2EX6 enzyme which explains its potent antibacterial activity in comparison with standard ampicillin. Keywords: Hydroxyacetyl, heterocycle, Naphthyl, Biological, Docking, 1DXO active site